SDG Pulse 2025 - UN Trade; Development (United Nations, 2025)
The SDG Pulse Series is UNCTAD’s annual statistical publication reporting on developments relating to the 2030 Agenda for Sustainable Development and the Sustainable Development Goals (SDGs). The purpose of this series is to: provide an update on the evolution of a selection of official SDG indicators and complementary data and statistics; provide progress reports on the development of new concepts and methodologies for UNCTAD custodian indicators. This series aims to showcase, beyond the perspective of the formal SDG indicators, how UNCTAD is contributing to the implementation of 2030 Agenda. Released annually, each version of the SDG Pulse highlights a thematic issue of immediate relevance to the 2030 Agenda.